Reduced cortical bone density with normal trabecular bone density in girls with Turner syndrome. - Holroyd, C; Davies, J; Taylor, P; Jameson, K; Rivett, C; Cooper, C; Dennison, E (2010)
SUMMARY: This study of 22 girls with Turner syndrome (TS) demonstrates a reduction in bone mineral apparent density (BMAD) at the femoral neck along with a reduction in cortical bone density at the radius (with sparing of trabecular bone). These findings may account for the increased fracture risk noted in this population. INTRODUCTION: Increased fracture risk is a feature of TS; however, the reasons for this are unclear. Little is known regarding cortical and trabecular bone mineral density (BMD) in TS. We have addressed this by measurement of volumetric bone mineral density (vBMD) using peripheral quantitative computed tomography (pQCT). METHODS: We studied 22 females with TS and 21 females without TS; mean ages 12.7 and 12.9 years, respectively. Bone mass measurements were made by dual-energy X-ray absorptiometry (DXA) of the lumbar spine and femur and pQCT of the radius. BMAD was calculated from DXA values. We utilized published reference data to generate Z-scores for both populations. RESULTS: The mean BMAD Z-score at the lumbar spine was not significantly different in individuals with TS compared to the controls. At the femoral neck, individuals with TS had a significantly lower BMAD Z-score compared to the controls (-1.32 vs. -0.14, p = 0.001). At the distal radius, total vBMD Z-score and trabecular vBMD Z-score were not significantly different between the TS group and controls. A significant reduction in cortical vBMD at the proximal radius was noted in the TS group however (-2.58 vs. -1.38, p = 0.02). There was also a trend towards reduced cortical thickness at this site in the TS group (Z-score -2.89 vs. -1.73, p = 0.08). DISCUSSION: TS is associated with reduced BMAD at the femoral neck; pQCT data suggests that cortical density is reduced with sparing of trabecular bone. This differential of cortical and trabecular BMD may predispose to fracture.